Gender Differences in Service Utilization and Pattern of Free Presbyopia Glasses Distribution among Patients at Eye Camps in Nepal: An Observational Study - Ranjan Shah; Sailesh Kumar Mishra; Pathiyil Ravi Shankar; Anup Subedi; Prakriti Sharma; Anil Paudel; Pankaj Ray Adhikari; Amit Kumar Singh (Journal of Nepal Medical Association)
Introduction: Presbyopia is an age-related refractive condition that causes difficulty in seeing nearby objects clearly. It affects a significant portion of the world’s population, especially individuals over 40 years old. Many studies show variation in the utilization of eye healthcare services according to gender in resource-limited settings like Nepal. This influence access to eye care service. This study aims to investigate gender-based differences in service utilization and prescription patterns at free presbyopia camps in Nepal.